Servant-leadership and forgiveness how leaders help heal the heart of the world - Song, Jiying, 1976-; Tran, Dung Q., 1979-; Ferch, Shann Ray, 1967-; Spears, Larry C., 1955- (State University of New York, 2020)
"A compelling gathering of perspectives on the intersection of servant-leadership and forgiveness"--